PENGARUH MODEL PEMBELAJARA TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM EKSKRESI DI KELAS VII SMP NEGERI 1 LAHUSA - Laia, Ariani (Universitas Nias Raya, 2023)
This study aims to determine the effect of the jigsaw cooperative learning model on student learning outcomes in excretion system material in class VII SMP Negeri 1 Lahusa. The method or type of research to be carried out is quantitative research with quasi-experimental methods. This research is said to be a pure experiment because all variables can be controlled. Quantitative research is a type of research that produces discoveries that can be achieved or obtained using statistical procedures or other methods of quantification/measurement. The population in this study were all 160 grade VII students of SMPN 1 Lahusa in the 2022/2023 academic year. while the samples in this study were class VII A as the experimental class and one class VII B as the control class. The experimental class in this study were students who used the jigsaw cooperative learning model while the control class were students who used the lecture method. The results of the study revealed that the learning outcomes of Science-Biology using the jigsaw type cooperative learning model were higher than learning using the lecture method. This can be seen from the data analysis of the two groups using the t-test, the results obtained are t-count 7.42 and in t-table at a significance level of 5% of 2.00, then t-count> t-table. This shows that there is an influence of the jigsaw cooperative learning model on student learning outcomes in science-biology subjects.